Pros and cons of Increasing Gadgets’ Usage in Medical Students of Pakistan - Tehseen haider (Students' Supplement of Journal of Rawalpindi Medical College, 2022)
The use of technological gadgets is growing at an unprecedented pace all over the world for the past few decades. In present times, dependency on these devices and the services provided by them has greatly increased in all age groups and work professions. According to the recent statistics for the year 2021, in a population of 223 million, 77.7% of people owned mobile connections; 64 million people had internet access and 46 million used social media platforms.1 Almost 10 million smartphone users have been added to the list in a single year.2 As our topic suggests, we will mainly focus on gadget overuse especially mobile phones among medical students in Pakistan. According to the literature, almost 96% of medical students in Islamabad and 100% of medical students in Lahore were using their smartphones.3,4 These above-mentioned statistics and percentages clearly define the importance of these devices in our lives. They have become part and parcel of our day-to-day routine in the true sense. Here are a few reasons enlisted:  There is a great revolution in teaching methods over the past few decades. We have transcended from the traditional methods of teaching to a whole new digitalised and internet-driven world of gaining knowledge. Previously used methods though were cheaper but provided limited access to information at a given time while the modern techniques not only have grabbed the interests of medical students but also have issued them with a better understanding and vast amount of knowledge via internet access, videos, online lectures, and books. It has put an end to all the limitations and boundaries in attaining knowledge. Hence it’s not wrong to say that every type of information is just one click away.  Along with the teaching modalities, there is a complete shift in spending leisure time. Previously students used to spend their free time engaged in some sort of healthy out-door activity or hobbies like painting, gardening or board games but now the only thing that makes students satisfied and satiated is the use of mobile phones, playing videos games and spending their time over different social media platforms like Facebook, Twitter, Instagram, TikTok and many more to name.  Moreover, these electronic devices are also being used as methods of coping with stress and anxiety which is widely prevalent among medical students. So, technology has not just become the best source of entertainment but also a great escape for medical students in their stressful lives. In addition to this, the devotion of their working and studying hours to these devices has greatly escalated the time spent in front of the screen. This increased screen time is negatively correlated to physical activity and the physical and mental health of students. The greater the sitting hours in front of screen-based devices, the lower the physical activity of an individual. Thus promoting a greater prevalence of different physical and mental problems which are mentioned below  Physical problems: Excessive use of these gadgets can cause backache, headache, neck pain, sleep disturbances, stomach upset, eye strain, increased incidence of glasses wearers, obesity, and cancers.  Mental problems: Increased screen time significantly influences the mental health of the individual. Reduced concentrating ability, stress, and depression are particularly reported after long hours of gadget usage. It is positively associated with psychiatric comorbidity.  Social isolation: This is probably the worst effect of it. A person gets secluded from the things and people around that then positively contributes to mental and physical health deterioration. Although technology has silently crept into the intricacies of our life and has adversely affected the overall well-being of an individual but we have to admit it is providing great service to us by breaking geographical barriers and making information accessible. Any webinar, seminar, or session whether conducted within the premises of Pakistan or arranged in any foreign country can be attended while sitting in our bedrooms. Research activities have been made a doodle because of the easy availability of articles via different research engines. The Internet serves as an important learning tool in medical education by providing access to the latest evidence anytime and anywhere. It allows the learners to study at their own pace with convenience without the hassle of attending physical classes. It is especially useful for students of developing countries to keep abreast of ever-expanding knowledge bridging the gap resulting from a scarcity of resources. In short, science and technology came as a boon for us but it is our use that made them a curse. Undeniably these gadgets have become a necessity in our lives and cannot be pulled away; neither it is recommended to stop their use completely in order to keep pace with the ever-growing world but they definitely should be used appropriately and judiciously. Using electronic devices in a controlled way can limit the negative effects they are posing in our everyday lives and thus they can yield maximum benefit.